The Spectrum of Tigecycline-Induced Pancreatitis in Clinical Characteristics, Diagnosis, and Management - Pan J; Ye C; Zhou LZ; Li ZY; Wang J; He X; Chen SJ; Zhou GQ (International Journal of General Medicine, 2023)
Juan Pan,1 Chao Ye,2 Ling-Zhi Zhou,1 Zu-Yi Li,1 Juan Wang,2 Xin He,2 Shen-Jue Chen,2 Guang-Qing Zhou2 1Department of Pharmacy, Liuyang Hospital of Traditional Chinese Medicine, Changsha, Hunan, People’s Republic of China; 2Department of Pharmacy, The Third Hospital of Changsha, Changsha, Hunan, People’s Republic of ChinaCorrespondence: Chao Ye, Department of Pharmacy, The Third Hospital of Changsha, No. 176 Laodong West Road, Tianxin District, Changsha, Hunan, 410015, People’s Republic of China, Email yechao1234256@163.com Ling-Zhi Zhou, Department of Pharmacy, Liuyang Hospital of Traditional Chinese Medicine, No. 67, Beizheng Middle Road, Changsha, Hunan, 410300, People’s Republic of China, Email 1024482174@qq.comIntroduction: Tigecycline-induced acute pancreatitis (AP) has been frequently increasingly reported in solid organ transplant patients. This review aimed to summarize the characteristics, possible mechanisms, and management of tigecycline-induced AP.Methods: Case reports of tigecycline-induced AP published in Chinese or English were collected until February 2023 for retrospective analysis.Results: Thirty-four patients from 29 articles were included. Fifteen patients (46.9%) had solid organ transplantation, and 4 patients (12.5%) had malignant tumors. Twenty-five patients (89.3%) received a recommended maintenance dose of tigecycline (50 mg q12 h). The median age was 50 years (range 9– 87). Compared to the nontransplant patients, the median age of the transplant patients was significantly younger, 44 years (range 12.5– 61) versus 57.5 years (range 9– 87) (P=0.03). The median time of symptom onset was 7 days (range 2– 29), and 91.2% (31/34) were less than 14 days. Typical initial symptoms included abdominal pain (90.6%), nausea (46.9%), vomiting (43.8%), and abdominal distention (21.9%). Most cases were accompanied by elevated levels of pancreatic enzymes. The main radiological features included edematous infiltrate and acute pancreatitis on computed tomography (CT) scan and abdominal ultrasound. Except for one patient who continued tigecycline treatment, all patients discontinued treatment and received symptomatic support such as fasting, acid suppression, and enzyme suppression. The median time to recover pancreatic enzymes to the normal range was 5 days (range 1– 43), and the median time to relieve symptoms was 4 days (range 1– 12). Four patients died, of whom two died of severe pancreatitis complications and two of cardiogenic shock and septicemia.Conclusion: Tigecycline-induced AP was a rare and serious complication that occurred mainly within two weeks of the medication. This serious side effect should be kept in mind while treating severe infections especially in transplant recipients.Keywords: tigecycline, pancreatitis, adverse drug reaction, solid organ transplantation